Immediate 1-month efficacy of desmopressin and anticholinergic combination therapy versus desmopressin monotherapy in the treatment of pediatric enuresis: A meta-analysis. Issue 3 (June 2016) - Chua, Michael E.; Silangcruz, Jan Michael A.; Chang, Shang-Jen; Yang, Stephen S.
Summary: Background: Several studies have proposed the combination of desmopressin and anticholinergic as a treatment regimen to address the pathophysiology of polyuria and bladder dysfunction in pediatric enuresis. However, the available literature is inconsistent with regards to the immediate 1-month efficiency of the combination therapy in the treatment for pediatric enuresis. Objective: The aim was to assess the immediate 1-month efficacy and safety of desmopressin and anticholinergic agent combination therapy versus desmopressin monotherapy in the treatment of pediatric enuresis using meta-analysis of randomized controlled trials (RCTs). Study design: Systematic literature acquisition was carried out on electronic medical databases up to April 2015. RCTs relevant to the topic were critically appraised. Dichotomous data of the 1-month post-treatment response rate (defined as ≥90% reduction of wet nights) were extracted for calculation of the risk ratio (RR) and 95% confidence interval (CI). The Mantel–Haenszel method with the random effects model was used to pool effect estimates. Inter-study heterogeneity and publication bias were assessed. Subgroup analysis was done for the desmopressin treatment-naive versus treatment-resistant groups: PROSPERO (CRD42015017922). Results: Four RCTs of good methodological quality without heterogeneity were included for meta-analysis. The pooled effect estimates showed that combination therapy was associated with a significantly better immediate 1-month response rate than desmopressin monotherapy. Subgroup analysis showed a greater immediate 1-month response rate among desmopressin-resistant patients than treatment-naive patients. No severe adverse events were noted among combination therapy treated groups. Discussion: The limitation of the current meta-analyses is the small sample size, albeit with high-quality studies pooled for effect estimation. Despite the limitation, the study results were able to consistently illustrate a large treatment effect of combination therapy among desmopressin treatment-resistant patients. It was consistent with the literature review of retrospective and non-comparative studies by Alloussi et al. (2011), who summarized a similar impressive treatment outcome. However, due to the low level of evidence available at the time of their study, only a grade B–C recommendation was given to combination therapy as an approach for second-line treatment. This study also summarized that combination therapy was well tolerated and similar to desmopressin monotherapy. Conclusion: This study was able to summarize the immediate 1-month efficacy of combination therapy compared with desmopressin monotherapy in the treatment of pediatric enuresis. For both treatment-naive and desmopressin-resistant pediatric enuresis, combination therapy of desmopressin with an anticholinergic agent is well tolerated and resulted in a significantly better immediate 1-month response rate than desmopressin monotherapy. Table Summary table of meta-analysis pooled effect estimate (Risk Ratio) on combination therapy versus Monotherapy. Immediate 1-month response rate comparison Combination therapy Monotherapy Risk ratio 95% CI >90% response rate Total subject >90% response rate Total subject Treatment naive 49 101 28 102 1.74 (1.20–2.52) Treatment resistant 16 79 4 75 3.77 (1.32–10.77) Overall total treatment effect 65 180 32 177 1.89 (1.34–2.68) Note heterogeneity and sensitivity tests: tau square = 0, chi square = 2.52; p = 0.47; I 2 = 0%. Total overall effect: Z = 3.59 ( p = 0.0003).